2014
DOI: 10.1177/0300060514541829
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic syndrome, adiponectin and proinflammatory status in patients with type 1 diabetes mellitus

Abstract: Objectives: To assess the prevalence of metabolic syndrome and evaluate proinflammatory status in patients with type 1 diabetes, and to analyse the relationship between inflammation, metabolic control and insulin resistance in these patients. Methods: Patients with type 1 diabetes were stratified according to the presence or absence of metabolic syndrome. Serum adiponectin, leptin, tumour necrosis factor (TNF)-a, interleukin (IL)-6 and high-sensitivity C-reactive protein (hsCRP) were quantified. Results: The p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
22
1
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(28 citation statements)
references
References 39 publications
2
22
1
3
Order By: Relevance
“…Other investigators have reported that adiponectin levels are higher in patients with type 1 diabetes compared to non-diabetes controls [3943]. The observations from the current study that adiponectin levels decreased from baseline with both BIL and glargine treatment are also concordant with literature showing that adiponectin levels decline with intensification of insulin treatment [4244]. In summary, the current data confirm that patients with type 1 diabetes may have high adiponectin levels, but whether lower levels of adiponectin are associated with insulin resistance or clinical cardiovascular disease cannot be confirmed.…”
Section: Discussionsupporting
confidence: 91%
“…Other investigators have reported that adiponectin levels are higher in patients with type 1 diabetes compared to non-diabetes controls [3943]. The observations from the current study that adiponectin levels decreased from baseline with both BIL and glargine treatment are also concordant with literature showing that adiponectin levels decline with intensification of insulin treatment [4244]. In summary, the current data confirm that patients with type 1 diabetes may have high adiponectin levels, but whether lower levels of adiponectin are associated with insulin resistance or clinical cardiovascular disease cannot be confirmed.…”
Section: Discussionsupporting
confidence: 91%
“…Adiponectin can exert both proinflammatory and anti-inflammatory effects [31,32] . In metabolic diseases, TNF-α and IL-6, which are secreted from mast cells in the skin and from macrophages in adipose tissue, are implicated in inhibition of the local production of adiponectin [33,34] .…”
Section: Discussionmentioning
confidence: 99%
“…3 The literature revealed that a high insulin dosage was often associated with increased risk of hypoglycemia, weight gain, and, in some cases, the aggravation of cardiovascular risk factors, including dyslipidemia. 4 Metformin is the first-line oral hypoglycemic agent commonly used in the treatment of type 2 diabetes mellitus (T2DM). 5 It decreases the glucose level primarily by suppressing hepatic glucose production (hepatic gluconeogenesis).…”
Section: Introductionmentioning
confidence: 99%